PENYELESAIAN SENGKETA PERTANAHAN OLEH KEPALA DESA SEBAGAI MEDIATOR DI DESA MARIHAT BANDAR KECAMATAN BANDAR KABUPATEN SIMALUNGUN - Ahsani, Ichsan Aulia; Sulaiman, Sulaiman; Basri, Hasan (Jurnal Ilmiah Mahasiswa Fakultas Hukum Universitas Malikussaleh, 2024)
Land issues in the community continue to increase and become more complex. In Marihat Bandar village, land disputes often occur, usually caused by disputes related to the transfer or seizure of land and the distribution of inheritance, especially land, is also a source of conflict. This land dispute requires a complete and fair resolution for the parties involved. The Village Head has an important role as a mediator in resolving land disputes in his village, in accordance with applicable laws. Based on Article 26 paragraph 4 letter k of Law Number 6 of 2014 concerning Villages, the Village Head is obliged to resolve disputes in his village. This confirms that non-litigation dispute resolution, such as mediation, can be carried out by the Village Head as part of carrying out his obligations. With three (3) aspects being studied including dispute resolution mechanisms, obstacles to mediation by the Village Head, and solutions to overcome them. The purpose of this study is to analyze in depth and examine how the mechanisms, obstacles, and solutions faced in the implementation of mediation carried out by the Village Head in resolving land disputes in Marihat Bandar Village. In addition, through this study, it is expected to find patterns that can be applied to improve the efficiency and success of mediation at the village level. This study uses an empirical legal research method. The empirical legal research method is a study conducted by means of field surveys and conducting interviews as a means of main data. This research is descriptive. observation and interviews. The results of the study showed that in Marihat Bandar village two land disputes were successfully resolved through mediation, while one dispute remained unresolved. Mediation was carried out in several stages, namely: Pre-mediation, Mediation, and Agreement Results. However, the peace agreement reached did not have permanent legal force because it was only made in the form of a Mediation Report (BAM) by the Village Head, without a peace deed registered with the District Court. The obstacles to mediation include a lack of legal understanding by both parties, interference from outside parties, and limited human resources (HR) in the village office who have legal and negotiation expertise. The solution is to improve community legal literacy and create a peace deed. The village government is expected to hold regular legal counseling programs involving legal practitioners to improve residents' understanding of land law. In addition, training and workshops for village officials are very important to improve their ability in negotiation and legal understanding, so that they are more effective in mediating disputes.